2016
DOI: 10.1103/physrevlett.116.015502
|View full text |Cite
|
Sign up to set email alerts
|

Self-Amplification of Solid Friction in Interleaved Assemblies

Abstract: It is nearly impossible to separate two interleaved phonebooks when held by their spines. A full understanding of this astonishing demonstration of solid friction in complex assemblies has remained elusive. In this Letter, we report on experiments with controlled booklets and show that the force required increases sharply with the number of sheets. A model captures the effect of the number of sheets, their thickness and the overlapping distance. Furthermore, the data collapse onto a selfsimilar master curve wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
28

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 24 publications
2
30
0
28
Order By: Relevance
“…A expressão entre parênteses, em (14), é igual a M v cm,cm , e como v cm,cm = 0, segue a igualdade (13) − o que conclui nossa demonstração da igualdade (6), partindo da igualdade (4).…”
Section: Teoremas Trabalho -Energia Cinéticaunclassified
See 2 more Smart Citations
“…A expressão entre parênteses, em (14), é igual a M v cm,cm , e como v cm,cm = 0, segue a igualdade (13) − o que conclui nossa demonstração da igualdade (6), partindo da igualdade (4).…”
Section: Teoremas Trabalho -Energia Cinéticaunclassified
“…Não posso deixar de comentar que o tema "atrito" ainda envolve muita investigação científica, e em um nível de sofisticação bastante superior às modelagens que foram discutidas neste artigo. Como apontam Alarcón e colaboradores [4], esforços em micro e nanoescalas e na biologia, durante as últimas décadas, têm resultado no ressurgimento de atividades na área de tribologia. 11 Se for de seu interesse, veja, por exemplo, as referências 5 a 15, na publicação de Alarcón e colaboradores, e artigos relacionados.…”
Section: Conclusão E Comentários Adicionaisunclassified
See 1 more Smart Citation
“…Performing indentation experiments, we observe an exponential growth of the resistance force with the product of the indentation depth by the square root of the number of beads per chain. The first factor is reminiscent of the selfamplification of friction in a capstan [17], as well as in interleaved books [18,19], where the increase in resistance is created by, and proportional to, the force exerted by the operator. The second factor points towards the central role played by inter-chain topological constraints, as in polymer physics [20].…”
mentioning
confidence: 99%
“…Previous studies about self-amplified friction in complex assemblies have shown that the frictional resistance essentially grows exponentially with the relevant control parameter, e.g. the angle in a capstan [17], or the Hercules number [18,19] in interleaved books. This general behaviour is intimately rooted in the fact that the increase in the force exerted by the operator is proportional to that force itself and to an effective coefficient of friction induced by the specific geometry.…”
mentioning
confidence: 99%